2010
DOI: 10.1007/s00227-010-1551-0
|View full text |Cite
|
Sign up to set email alerts
|

How do nutrient conditions and species identity influence the impact of mesograzers in eelgrass-epiphyte systems?

Abstract: 26Coastal eutrophication is thought to cause excessive growth of epiphytes in eelgrass beds, 27 threatening the health and survival of these ecologically and economically valuable 28 ecosystems worldwide. Mesograzers, small crustacean and gastropod grazers, have the 29 potential to prevent seagrass loss by grazing preferentially and efficiently on epiphytes. We 30 tested the impact of three mesograzers on epiphyte biomass and eelgrass productivity under 31 three fold enriched nutrient concentrations in experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
(66 reference statements)
0
10
0
Order By: Relevance
“…However, the increased snail density and biomass under enriched conditions may have enhanced competition for food leading to a situation, where snails were similarly resource limited irrespective of enrichment level. In addition, it is also possible that these results largely reflect both qualitative and quantitative effects within the algae (Jaschinski and Sommer 2011). In this sense, see also Kraufvelin et al (2006a), where a path analysis showed that indirect effects on G. locusta density from nutrients via green algae were 50% bigger than direct nutrient treatment effects on gammarid abundance.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, the increased snail density and biomass under enriched conditions may have enhanced competition for food leading to a situation, where snails were similarly resource limited irrespective of enrichment level. In addition, it is also possible that these results largely reflect both qualitative and quantitative effects within the algae (Jaschinski and Sommer 2011). In this sense, see also Kraufvelin et al (2006a), where a path analysis showed that indirect effects on G. locusta density from nutrients via green algae were 50% bigger than direct nutrient treatment effects on gammarid abundance.…”
Section: Discussionmentioning
confidence: 91%
“…L. littorea is found on rocky shores at the East and West Atlantic coasts, preferentially at low shore levels (Norton et al 1990;Carlson et al 2006;Perez et al 2009). Although the feeding preferences of L. littorea are mainly restricted to early successional stages of perennial macroalgae, diatoms, and ephemeral green algae (Norton et al 1990; Wilhelmsen and Reise 1994;Jaschinski and Sommer 2011), the species has also been characterized as an omnivorous grazer (Chang et al 2011) that can even feed on barnacle larvae (Wahl and Sönnichsen 1992;Buschbaum 2000). The feeding activity of littorinids seems to be influenced by several factors such as body mass, water temperature, and tides (Newell et al 1971;Norton et al 1990).…”
Section: Introductionmentioning
confidence: 98%
“…However, extensive previous work shows that grazing by invertebrates such as amphipods and isopods in temperate seagrass beds can counteract algal overgrowth, thus fostering dominance by seagrasses, and that grazing has effects of similar or greater magnitude to water column nutrient enrichment (Neckles et al 1993, Hughes et al 2004. While grazing has the potential to counter the effects of water column nutrient enrichment in some circumstances (Neckles et al 1993, Hays 2005, Jaschinski & Sommer 2011, Zostera habitats in Chesapeake Bay are increasingly faced with multiple simultaneous stressors whose interactions are poorly understood and difficult to predict (Orth et al. 2006).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…; Moksnes et al . ; Jaschinski & Sommer ). Some good reviews dealing with the magnitude of nutrient enhancement and grazing effects in epiphyte biomass are available (Orth & VanMontfrans ; Hughes et al .…”
Section: Introductionmentioning
confidence: 99%
“…), along with hydrodynamics (Schanz et al . ) and resource availability in the system (Russell & Connell ; Jaschinski & Sommer ; McSkimming et al . ), determine grazing intensity on epiphytes in seagrass ecosystems.…”
Section: Introductionmentioning
confidence: 99%